Analysis Of Mefenamic Acid Residue In Urine Of Herbal Madicine For Aches and Pains Consumers Using Ultraviolet-Visible Spectrophotometry Method - Anik Eko Novitasari; Ria Ratna Amelia (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Mefenamic acid is the chemical drug that has been added to herbal medicine. With the presence of these chemical additives that are not controlled will be harmful to society. So it is necessary to determine the presence of residual mefenamic acid content in the urine of consumption of herbal medicine aches and pains by ultraviolet-visible spectrophotometry. The sampling technique in this study used the Non-Probability Sampling technique with a total of 30 urine samples consuming stiff rheumatic herbs in Desa Panggang, Glagah, Lamongan. Based on the research that has been done, it was found that 30 urine samples of consuming herbal medicine A, B, C, and D were positive for the chemical mefenamic acid with the highest level of 7.16% and the lowest level of 2.17%. From the results of the analysis of the normality test and homogeneity test, it is obtained that the data are normally distributed and homogeneous. Based on the results of the Independent T Test, the value of Sig. (2-tailed) of 0.000 <0.05, which means that there is a mefenamic acid content in the urine of those who consume herbal medicine aches and pains.